Inflammatory Pseudotumor of the Temporal Bone: A Case Series. Issue 7 (August 2017) - Ortlip, Timothy E.; Drake, Virginia E.; Raghavan, Prashant; Papadimitriou, John C.; Porter, Neil C.; Eisenman, David J.; Hertzano, Ronna
Abstract : Objective: Inflammatory pseudotumor of the temporal bone is a benign, idiopathic inflammatory process that is locally invasive and a cause of significant morbidity. This study reviews our experience with seven patients and is currently the largest series to date. Study Design: Retrospective review from January 1, 2014 to January 1, 2016. Setting: Single tertiary medical center. Patients: There were five male and two female (n = 7) subjects with a diagnosis of temporal bone inflammatory pseudotumor. The mean age at presentation was 41 years old. The most common presenting symptoms were hearing loss (7/7) and headache (4/7). Four patients demonstrated an inflammatory aural polyp. Two patients experienced facial nerve paralysis. Intervention(s): Seven patients underwent computed tomography and six underwent magnetic resonance imaging. Corticosteroids and antibiotics were the initial treatment of choice. Five patients also underwent surgery. As adjuvant therapy, two patients received Rituximab, one patient received radiation, and one received mycophenolate mofetil. Main Outcome Measure(s): Clinical courses were followed with focus on symptoms, disease recurrence, duration, and treatment. Mean follow-up was 17.8 months. Results: The primary lesions demonstrated T2 hypo-intensity and enhancement as well as diffuse dural thickening on magnetic resonance imaging in five of six patients. Histopathology demonstrated chronic inflammation in the setting of hyalinized fibrosis (7/7). All the patients are currently symptomatically stable. Conclusion: Inflammatory pseudotumor of the temporal bone can cause devastating effects on neurological function and quality of life. Recognition of characteristic imaging and histopathology can expedite appropriate treatment. Patients may require chronic steroid therapy. Adjunctive therapy with radiation and immuno-modulation are currently being explored.